Pengabdian Masyarakat Pelatihan Membuat Perjanjian Kredit Barang (Mindring) - Aknes Galih Sumirat; Febrilia Rustina Arfiani; Muhamad Rois Nova Rona; Rina Arum Prastyanti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Mindring is a business carried out by someone who sells goods using an installment payment system. In the mindring activity itself, it is actually very necessary to have a written agreement between the business actor and the buyer to provide legal certainty to the parties. The method used in carrying out the service is by presenting the material through a lecture, after completing the presentation of the material there is a discussion and question and answer session. Based on the results of the service we carried out, it shows that the implementation of credit for goods (mindring) in villages is still widely carried out by mothers in order to meet the need for household furniture, this is done because the payment system can be done online. However, the problem is that this agreement still uses an oral agreement, where if one day there is fraud or default, one of the aggrieved parties cannot have strong evidence for court proceedings. Therefore, this community service can help residents in the process of crediting goods by making written agreements.